Rekontruksi Tujuan, Materi dan Strategi Pembelajaran PAI di Era Society 5.0 - Hapni Madinah Al Zahra Pohan; Alvi Zakiyah Putri; Juni Erpida (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of digital technology in the Society 5.0 era has significant implications for the education system, including Islamic Religious Education (PAI) learning. This era places humans at the center of technological development, thus demanding Islamic education to remain relevant, adaptive, and oriented towards humanitarian values. This study aims to analyze and reconstruct the objectives, materials, and strategies of Islamic Religious Education (PAI) learning to align with the characteristics and challenges of the Society 5.0 era. This study uses a literature review approach through a review of various scientific sources in the form of books, articles, and other sources. The results of the study indicate that the reconstruction of Islamic Religious Education (PAI) learning encompasses three main aspects. First, the learning objectives are directed at developing students who are faithful, have noble character, possess 21st-century competencies, and are able to utilize technology wisely. Second, Islamic Religious Education (PAI) learning materials need to be developed adaptively, contextually, and integrated with digital technology without eliminating the foundation of the Qur'an and Hadith. Third, Islamic Religious Education (PAI) learning strategies in the Society 5.0 era emphasize a humanistic, participatory approach, discovery learning, and blended learning that combines face-to-face and digital learning. This reconstruction is expected to produce a relevant, innovative Islamic Religious Education (PAI) learning model that is oriented toward character building and strengthening Islamic values ​​amidst modern technological developments.